Preparing Pharmacists for The Era of AI-driven Pharmacological Sciences: An Opinion Article - Urfa Khairatun Hisan; Rizqi Dinni Fauzia; Muhammad Miftahul Amri (Journal of Pedagogy and Education Science, 2023)
Due to its rapid development, artificial intelligence (AI) has gained a lot of popularity in many sectors, including pharmacological sciences. In pharmacological sciences, AI has been applied in various areas, from AI-driven drug discovery and genomic sequencing to the development of personalized medicine. Subsequently, the need for pharmacists with adequate AI-related skills and knowledge increases. However, the current traditional curriculum of pharmacy education does not cover AI courses. To elaborate on the current developments in AI-driven pharmacology and present the discussion of the possibility of whether AI-related courses should be included in the current curriculum. We have gathered 32 references on AI-driven pharmacological applications, pharmacy curricula, and the future trends of pharmacological sciences. The literature is obtained from online databases such as Scopus, PubMed, IEEE, and Google Scholar. Based on the literature reviews, we presented the discussion and scientific-based opinion on the need for AI-related courses in the school of pharmacy. We believe that AI will be the basis of future pharmacological development. Hence, we consider that it is the right time to include AI-related courses in the student's curriculum to prepare future-proof pharmacists.